Low substrate temperature deposition of amorphous and microcrystalline silicon films on plastic substrates by hot-wire chemical vapor deposition - Alpuim, P. (2000)
Amorphous and microcrystalline silicon films were deposited by radio-frequency plasma enhanced chemical vapor deposition (rf-PECVD) and hot-wire chemical Vapor deposition (HW-CVD) on plastic (polyethylene terephthalate-PET) at 100 degrees C and 25 degrees C. Structural properties of these films were measured by Raman spectroscopy. Electronic properties were measured by dark conductivity and photoconductivity. For amorphous silicon films deposited by rf-PECVD on PET, photosensitivities > 10(5) were obtained at both 100 degrees C and 25 degrees C, For amorphous silicon films deposited by HW-CVD, a photosensitivity of > 10(5) was obtained at 100 degrees C. Microcrystalline silicon films deposited by HW-CVD at 95% hydrogen dilution had sigma(ph) similar to 10(-4) Omega(-1) cm(-1), while maintaining a photosensitivity of similar to 10(2) at both 100 degrees C and 15 degrees C. Microcrystalline silicon films with a large crystalline fraction (>50%) can be deposited by HW-CVD all the way down to room temperature. All the films had good adhesion and mechanical stability as neither adhesive nor cohesive failure was observed even when the substrates were bent elastically.